2018
DOI: 10.2174/1381612823666171024155811
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Spectra of Nucleoside Phosphorylases and their Potential in the Production of Pharmaceutically Active Compounds

Abstract: Nucleoside phosphorylases are valuable tools to produce modified nucleosides with therapeutic or diagnostic potential with high affinity and specificity. A wide variety of nucleoside phosphorylases are available in nature which differ in their protein sequence and show varying substrate spectra. To overcome limitations of the naturally occurring enzymes site-directed mutagenesis approaches can be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 0 publications
0
44
0
Order By: Relevance
“…NPases catalyze the phosphorolysis of nucleosides to pentose‐1‐phosphates, as well as the corresponding reverse reaction (Scheme ). They are generally classified as either pyrimidine nucleoside phosphorylases (Py‐NPases) or purine nucleoside phosphorylases (Pu‐NPases), depending on their substrate spectra …”
Section: Introductionmentioning
confidence: 99%
“…NPases catalyze the phosphorolysis of nucleosides to pentose‐1‐phosphates, as well as the corresponding reverse reaction (Scheme ). They are generally classified as either pyrimidine nucleoside phosphorylases (Py‐NPases) or purine nucleoside phosphorylases (Pu‐NPases), depending on their substrate spectra …”
Section: Introductionmentioning
confidence: 99%
“…Numerous reviews on nucleoside phosphorylases are available. The structural organization of these enzymes [1,2], the substrate specificity and methods for the synthesis of valuable nucleosides [3][4][5][6], and metabolism in biological systems [7][8][9][10] have been considered.…”
Section: Nucleoside Phosphorylases As Key Enzymes In Nucleoside Metabmentioning
confidence: 99%
“…PNP is responsible for the regulation of the nucleoside concentrations within the living cells, and it is a target of various types of pharmaceutical interventions [12,13], including gene therapy of some inherited immunological deficiencies [14] and gene therapy of solid tumors [15]. Additionally, PNP's from various sources are utilized as biocatalysts in chemo-enzymatic syntheses of various nucleoside analogs of pharmaceutical and/or analytical significance [16][17][18][19][20]. Our previous investigations have shown that PNP isolated from E. coli, which is known to possess a broad specificity toward various base and nucleoside analogs [16], is also active toward many tri-cyclic nitrogen bases, derived from adenine and guanine [17,21,22], producing in the phosphate free media many potentially useful ribosides, using β-d-ribose-1-phosphate (R1P) as a ribose source.…”
Section: Introductionmentioning
confidence: 99%